Rare earth metal element doped silicon steel sheet and preparation method thereof
Through the combination of rare earth metal element doping and silicone modified polyurethane coating, the corrosion problem of silicon steel sheets in harsh environments is solved, significantly improving its corrosion resistance and adhesion properties, extending equipment life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411806318.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Silicon steel sheets are prone to corrosion in harsh environments, resulting in reduced mechanical properties and equipment failures. The existing technology is difficult to effectively improve its corrosion resistance and coating adhesion properties.
Silicon steel sheets doped with rare earth metal elements are prepared and pretreated silicon steel sheets are prepared through vacuum smelting, hot rolling processing and other processes. Silicone modified polyurethane coating is used to add modified silica, fluorine-containing solutions and silanized epoxy resins. , a coating with good adhesion and corrosion resistance was prepared.
It significantly improves the corrosion resistance and coating adhesion of silicon steel sheets, extends the service life of the equipment, reduces maintenance costs, and maintains excellent performance in high humidity and temperature changes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrical steel manufacturing, in particular to a rare earth metal element-doped silicon steel sheet and a preparation method thereof. Background Art
[0002] Silicon steel sheet, also known as electrical steel sheet, is a special steel material containing a certain proportion of silicon. It has excellent magnetic properties, low iron loss, high magnetic permeability and other characteristics, and is widely used in the fields of power, electronics and electrical equipment manufacturing. With the rapid development of modern science and technology, the role of silicon steel sheet in the industrial and energy fields has become more and more significant, mainly reflected in: 1. In modern power systems, the manufacture of high-efficiency transformers is highly dependent on silicon steel sheets. Especially in the field of renewable energy generation (such as wind power and solar energy), high-efficiency motors and transformers are the core of improving energy conversion efficiency. The low iron loss characteristics of silicon steel sheets help reduce energy loss during power transmission and conversion, thereby reducing carbon emissions, which is in line with the global trend of energy conservation and emission reduction.
[0003] 2. The rapid expansion of the new energy vehicle industry has put forward higher requirements for high-efficiency motors, and silicon steel sheets are one of the key materials for manufacturing high-efficiency motors. The high magnetic permeability and low iron loss characteristics of silicon steel sheets can effectively improve the energy efficiency of electric vehicle drive motors, extend the driving range, and reduce battery energy consumption. In addition, the excellent mechanical properties of silicon steel sheets can also improve the heat dissipation and durability of motors, adapt to the complex working environment of new energy vehicles, and further promote industrial upgrading.
[0004] 3. The wide application of silicon steel sheets in transformer manufacturing has directly promoted the efficiency improvement of power transmission and distribution systems. By reducing the energy loss of transformers during power transmission, silicon steel sheets can effectively improve the overall efficiency of the power grid, reduce power waste, and reduce energy costs.
[0005] However, silicon steel sheets are susceptible to corrosion when used in harsh environments (such as high humidity, large temperature changes, or contact with corrosive media). This corrosion will lead to a decrease in the mechanical properties of the metal, increase power loss, and in severe cases may cause equipment failure. Therefore, improving the corrosion resistance of silicon steel sheets is crucial to slowing down the corrosion process, extending the service life of equipment, and reducing replacement and maintenance costs. In addition, it is equally important to ensure the adhesion of the coating. Good adhesion can ensure that the coating is not easy to fall off during use, which is crucial for protecting the substrate from external erosion and improving wear resistance. The excellent adhesion of the coating can enable it to maintain its intended function in long-term operation and reduce the degradation of equipment performance caused by coating shedding.
[0006] In order to overcome the defects of the prior art, the present invention provides a rare earth metal element doped silicon steel sheet and a preparation method thereof. Summary of the invention
[0007] The object of the present invention is to provide a rare earth metal element doped silicon steel sheet and a preparation method thereof, so as to solve the problems in the prior art.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a rare earth metal element doped silicon steel sheet comprises the following steps: Step 1: subjecting the silicon steel raw material to vacuum smelting, hot rolling, normalizing heat treatment, high temperature heat treatment, cooling water quenching, tempering heat treatment, and pickling treatment in sequence to obtain a pretreated silicon steel sheet; Step 2: Dry the polytetrahydrofuran and hydroxypropyl terminated silicone oil at 120-130° C., then add diisobutyltin dioctanoate, hexamethylene diisocyanate and tetrahydrofuran, stir and react at 80-90° C. for 2-3 hours, then add modified silica solution, fluorine-containing solution and / or silylated epoxy resin, stir well at 80-90° C. for 2-3 hours, and after the reaction is completed, dry at 25-30° C. for 25-30 hours to obtain silicone-modified polyurethane; By adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution, an organosilicon-modified polyurethane A is prepared; by adding a modified silica solution and a fluorine-containing solution, an organosilicon-modified polyurethane B is prepared; Step 3: Mix and grind the organosilicon-modified polyurethane A, dispersing aid, rheological aid, barium sulfate precipitate, talcum powder and anti-corrosion pigment to obtain coating A; mix and grind the organosilicon-modified polyurethane B, dispersing aid, rheological aid, barium sulfate precipitate, talcum powder and anti-corrosion pigment to obtain coating B; apply coating A to the surface of the pretreated silicon steel sheet, and cure it at 180-200°C for 1-2h to obtain an adhesion layer; then apply coating B, and cure it at 180-200°C for 1-2h to obtain a corrosion-resistant layer.
[0009] More optimally, in step 1, the silicon steel raw material includes 7-10wt% Si, 0.7-1.0wt% Cu, 0.3-0.6wt% rare earth elements, and the balance is Fe.
[0010] More optimally, in step one, the rare earth element is any one of Ce, La, Y, Dy, and Nd; vacuum smelting: temperature is 1400-1600°C, time is 30-40min; hot rolling processing temperature is 900-1100°C; normalizing heat treatment: temperature is 900-1000°C, time is 10-20min; high temperature heat treatment: 900-1000°C, time is 1-2h; cooling water quenching treatment: cooling to 600-650°C and then cooling to 25-30°C by water quenching; tempering heat treatment: temperature is 200-300°C, time is 0.5-1h.
[0011] More optimally, in step 2, the contents of the components of the organosilicon-modified polyurethane are: by mass, 13-15 parts of polytetrahydrofuran, 25-30 parts of hydroxypropyl-terminated silicone oil, 0.005-0.007 parts of diisobutyltin dioctanoate, 18-25 parts of hexamethylene diisocyanate, 105-115 parts of tetrahydrofuran, 12-16 parts of modified silica solution, 14-19 parts of fluorine-containing solution and / or 18-28 parts of silanized epoxy resin solution.
[0012] More optimally, when preparing silicone-modified polyurethane A, the reaction mass ratio of modified silica, 2,3,5,6-tetrafluorophenylenedimethanol and silylated epoxy resin is 1:1.2:(1.5-1.7); when preparing silicone-modified polyurethane B, the reaction mass ratio of modified silica and 2,3,5,6-tetrafluorophenylenedimethanol is 1:(1.2-1.4).
[0013] More optimally, the modified nano-silica is dissolved in tetrahydrofuran to obtain a modified silica solution; 2,3,5,6-tetrafluorophenylenedimethanol is dissolved in tetrahydrofuran to obtain a fluorine-containing solution; and the silylated epoxy resin is dissolved in acetone to obtain a silylated epoxy resin solution.
[0014] More optimally, the preparation process of the silylated epoxy resin is as follows: in a nitrogen environment, epoxy resin and butyl acetate are mixed, heated to liquid at 40-50°C, 3-aminopropyltriethoxysilane is added, and the reaction is continued with stirring for 3-4 hours to obtain a silylated epoxy resin; wherein the reaction mass ratio of epoxy resin, butyl acetate and 3-aminopropyltriethoxysilane is 10:1:(1.0-1.5).
[0015] More optimally, the preparation process of the modified nano-silica is as follows: nano-silica filler and toluene are mixed, and the mixture is stirred evenly to obtain a nano-silica solution; 3-mercaptopropyltrimethoxysilane and toluene are mixed, and the mixture is stirred evenly to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution is heated to 100-110°C, and the 3-mercaptopropyltrimethoxysilane solution is added, and the reaction is continued for 10-14 hours. After the reaction is completed, the mixture is centrifuged, purified, and dried to obtain modified nano-silica; wherein the reaction mass ratio of the nano-silica filler and the 3-mercaptopropyltrimethoxysilane is 2:(5-6).
[0016] More optimally, in step three, the contents of the components of coating A are: by mass fraction, 65-75% silicone modified polyurethane A, 0.7-1.0% dispersing aid, 0.3-0.5% rheological aid, 5-7% barium sulfate precipitate, 5-7% talcum powder, and the balance is anti-corrosion pigment; the contents of the components of coating B are: by mass fraction, 65-75% silicone modified polyurethane B, 0.7-1.0% dispersing aid, 0.3-0.5% rheological aid, 5-7% barium sulfate precipitate, 5-7% talcum powder, and the balance is anti-corrosion pigment.
[0017] More optimally, in step three, the thickness of the adhesion layer is 40-60 μm, and the thickness of the corrosion-resistant layer is 90-100 μm.
[0018] Beneficial effects of the present invention: The present invention is characterized in that, in step 2, a silicone modified polyurethane is prepared by adding polytetrahydrofuran, hydroxypropyl-terminated silicone oil, diisobutyltin dioctanoate, hexamethylene diisocyanate, modified silica solution, fluorine-containing solution and / or silylated epoxy resin. The reaction mechanism of the process is: under the catalytic action of diisobutyltin dioctanoate, the hydroxyl groups of polytetrahydrofuran and hydroxypropyl-terminated silicone oil and the isocyanate groups of hexamethylene diisocyanate undergo polycondensation to obtain an isocyanate-terminated polyurethane intermediate; and further adding a modified silica solution, fluorine-containing solution and / or silylated epoxy resin solution containing hydroxyl groups to obtain a silicone modified polyurethane. The modified silica material can effectively block the penetration of corrosive media and enhance the corrosion resistance of the silicone modified polyurethane. The fluorine-containing material has an extremely low surface energy, which can significantly reduce the wettability of the material surface, making it more difficult for water and other corrosive liquids to spread and penetrate on the material surface, thereby improving the corrosion resistance of the material. Silylated epoxy resin contains more polar groups such as epoxy groups and hydroxyl groups, so it can effectively enhance the molecular polarity and improve the adhesion performance of the material surface.
[0019] The silylated epoxy resin is prepared by adding epoxy resin, butyl acetate and 3-aminopropyltriethoxysilane. In this step, 3-aminopropyltriethoxysilane is hydrolyzed to generate silanol groups and alcohols. Furthermore, the epoxy groups and silanol groups of the epoxy resin undergo a ring-opening reaction to obtain a silylated epoxy resin containing hydroxyl groups. By adding 3-mercaptopropyltrimethoxysilane, nano-silica filler and toluene, a mercapto-modified modified silica solution is obtained.
[0020] The present invention is characterized in that in step three, silicone modified polyurethane A is prepared by adding polytetrahydrofuran, hydroxypropyl-terminated silicone oil, diisobutyltin dioctanoate, hexamethylene diisocyanate, modified silica solution, fluorine-containing solution and silylated epoxy resin solution. In this step, a material with good adhesion and corrosion resistance is prepared by setting the reaction mass ratio of modified silica, 2,3,5,6-tetrafluorophenylenedimethanol and silylated epoxy resin to 1:1.2:(1.5-1.7). The material is prepared into a coating, which can significantly improve the polarity of the material, enhance the interaction between the coating and the pretreated silicon steel sheet, and improve the adhesion of the coating. Silicone modified polyurethane B is prepared by adding polytetrahydrofuran, hydroxypropyl-terminated silicone oil, diisobutyltin dioctanoate, hexamethylene diisocyanate, modified silica solution and fluorine-containing solution. This step can ensure that the reinforcing effect of the modified silica and the corrosion resistance of the fluorine element achieve an optimal balance by setting the reaction mass ratio of the modified silica and 2,3,5,6-tetrafluorophenylenediol to 1:(1.2-1.4), so that the coating has both excellent mechanical properties and corrosion resistance, thereby significantly improving the corrosion resistance of the surface of the pretreated silicon steel sheet. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Source of raw materials: Epoxy resin, provided by Jinan Zesheng Chemical Co., Ltd., model E51; nano-silica filler particle size of 0.8μm; polytetrahydrofuran, Mw=1000g / mol; hydroxypropyl terminated silicone oil, Mw=2000g / mol; dispersing aid, specifically LOPON 895 dispersing aid; rheological aid, specifically BENTONE LT rheological aid; talcum powder fineness of 400 mesh; anticorrosive pigment, provided by Guangzhou Si Tuyuan Chemical Co., Ltd., model Halox SZP-391; in terms of mass parts, one part is 1g.
[0023] Example 1: Step 1: The silicon steel raw material is subjected to vacuum smelting at 1600°C for 40 min, hot rolling at 1100°C, normalizing heat treatment at 1000°C for 20 min, high temperature heat treatment at 1000°C for 2 h, cooling to 650°C and then cooling to 30°C by water quenching, tempering heat treatment at 300°C for 1 h, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 50° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 4 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 110° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 14 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 6.4 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 130°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and the mixture was stirred at 90°C for 3h, and then a modified silica solution, a fluorine-containing solution and / or a silylated epoxy resin were added, and the mixture was fully stirred at 90°C for 3h. After the reaction was completed, the mixture was dried at 30°C for 30h to obtain an organosilicon-modified polyurethane; an organosilicon-modified polyurethane A was prepared by adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution; an organosilicon-modified polyurethane B was prepared by adding a modified silica solution and a fluorine-containing solution; Step 3: In terms of mass fraction, 75% of silicone modified polyurethane A, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating A; 75% of silicone modified polyurethane B, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating B; coating A is applied to the surface of the pretreated silicon steel sheet and cured at 200°C for 2h to obtain an adhesion layer with a thickness of 60μm; then coating B is applied and cured at 200°C for 2h to obtain a corrosion-resistant layer with a thickness of 100μm.
[0024] Example 2: Step 1: The silicon steel raw material is subjected to vacuum smelting at 1500°C for 35 minutes, hot rolling at 1000°C, normalizing heat treatment at 950°C for 15 minutes, high temperature heat treatment at 950°C for 1.5 hours, cooling to 625°C and then cooling to 27°C by water quenching, tempering heat treatment at 250°C for 0.7 hours, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 45° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 3.5 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 105° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 12 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 6.4 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 125°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and the mixture was stirred at 85°C for 2.5h, and then a modified silica solution, a fluorine-containing solution and / or a silylated epoxy resin were added, and the mixture was fully stirred at 85°C for 2.5h. After the reaction was completed, the mixture was dried at 27°C for 27h to obtain an organosilicon-modified polyurethane; an organosilicon-modified polyurethane A was prepared by adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution; an organosilicon-modified polyurethane B was prepared by adding a modified silica solution and a fluorine-containing solution; Step 3: In terms of mass fraction, 75% of silicone modified polyurethane A, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating A; 75% of silicone modified polyurethane B, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating B; coating A is applied to the surface of the pretreated silicon steel sheet, and cured at 190°C for 1.5 hours to obtain an adhesion layer with a thickness of 60 μm; then coating B is applied and cured at 190°C for 1.5 hours to obtain a corrosion-resistant layer with a thickness of 100 μm.
[0025] Example 3: Step 1: The silicon steel raw material is subjected to vacuum smelting at 1500°C for 30 minutes, hot rolling at 900°C, normalizing heat treatment at 900°C for 10 minutes, high-temperature heat treatment at 900°C for 1 hour, cooling to 600°C and then cooling to 25°C by water quenching, tempering heat treatment at 200°C for 0.5 hours, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 40° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 3 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 100° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 10 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 6.4 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 120°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and the mixture was stirred at 80°C for 2h, and then a modified silica solution, a fluorine-containing solution and / or a silylated epoxy resin were added, and the mixture was fully stirred at 80°C for 2h. After the reaction was completed, the mixture was dried at 25°C for 25h to obtain an organosilicon-modified polyurethane; an organosilicon-modified polyurethane A was prepared by adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution; an organosilicon-modified polyurethane B was prepared by adding a modified silica solution and a fluorine-containing solution; Step 3: In terms of mass fraction, 75% of silicone modified polyurethane A, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating A; 75% of silicone modified polyurethane B, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating B; coating A is applied to the surface of the pretreated silicon steel sheet and cured at 180°C for 1h to obtain an adhesion layer with a thickness of 60μm; then coating B is applied and cured at 180°C for 1h to obtain a corrosion-resistant layer with a thickness of 100μm.
[0026] Comparative Example 1: The reaction mass ratio of modified silicon dioxide and 2,3,5,6-tetrafluorophenylenedimethanol in the corrosion-resistant layer and the adhesion layer is adjusted to 1:0.7, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The silicon steel raw material is sequentially subjected to vacuum smelting at 1600°C for 40 minutes, hot rolling at 1100°C, normalizing heat treatment at 1000°C for 20 minutes, high-temperature heat treatment at 1000°C for 2 hours, cooling to 650°C and then cooling to 30°C through water quenching, tempering heat treatment at 300°C for 1 hour, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 50° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 4 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 110° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 14 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 2.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 6.4 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 130°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and the mixture was stirred at 90°C for 3h, and then a modified silica solution, a fluorine-containing solution and / or a silylated epoxy resin were added, and the mixture was fully stirred at 90°C for 3h. After the reaction was completed, the mixture was dried at 30°C for 30h to obtain an organosilicon-modified polyurethane; an organosilicon-modified polyurethane A was prepared by adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution; an organosilicon-modified polyurethane B was prepared by adding a modified silica solution and a fluorine-containing solution; Step 3: In terms of mass fraction, 75% of silicone modified polyurethane A, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating A; 75% of silicone modified polyurethane B, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating B; coating A is applied to the surface of the pretreated silicon steel sheet and cured at 200°C for 2h to obtain an adhesion layer with a thickness of 60μm; then coating B is applied and cured at 200°C for 2h to obtain a corrosion-resistant layer with a thickness of 100μm.
[0027] Comparative Example 2: The preparation step of the corrosion-resistant layer is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The silicon steel raw material is sequentially subjected to vacuum smelting at 1600°C for 40min, hot rolling at 1100°C, normalizing heat treatment at 1000°C for 20min, high-temperature heat treatment at 1000°C for 2h, cooling to 650°C and then cooling to 30°C by water quenching, tempering heat treatment at 300°C for 1h, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 50° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 4 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 110° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 14 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 6.4 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 130°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and stirred for reaction at 90°C for 3h, and then modified silica solution, fluorine-containing solution and silylated epoxy resin were added, and fully stirred for 3h at 90°C. After the reaction was completed, the mixture was dried at 30°C for 30h to obtain silicone-modified polyurethane; Step 3: Mix and grind 75% silicone-modified polyurethane, 1% dispersing agent, 0.5% rheological agent, 7% barium sulfate precipitate, 7% talcum powder and 9.5% anti-corrosion pigment by mass fraction to obtain a coating; apply the coating to the surface of the pretreated silicon steel sheet, and cure it at 200°C for 2h to obtain an adhesion layer with a thickness of 60μm.
[0028] Comparative Example 3: The reaction mass ratio of modified silica, 2,3,5,6-tetrafluorophenylenedimethanol and silylated epoxy resin in the adhesion layer is adjusted to 1:1.2:0.5, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The silicon steel raw material is sequentially subjected to vacuum smelting at 1600°C for 40 minutes, hot rolling at 1100°C, normalizing heat treatment at 1000°C for 20 minutes, high-temperature heat treatment at 1000°C for 2 hours, cooling to 650°C and then cooling to 30°C through water quenching, tempering heat treatment at 300°C for 1 hour, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Under a nitrogen environment, 10 g of epoxy resin and 1 g of butyl acetate were mixed, heated at 50° C. until liquid, and then 1.3 g of 3-aminopropyltriethoxysilane was added, and the reaction was continued by stirring for 4 h to obtain a silylated epoxy resin; 2 g of nano-silica filler and toluene were mixed and stirred to obtain a nano-silica solution; 5.5 g of 3-mercaptopropyltrimethoxysilane and toluene were mixed and stirred to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution was heated to 110° C., and the 3-mercaptopropyltrimethoxysilane solution was added, and the reaction was continued for 14 hours. After the reaction was completed, the modified nano-silica was obtained by centrifugation, purification, and drying; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 2 g of silylated epoxy resin was dissolved in 12 g of acetone to obtain a silylated epoxy resin solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 130°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and the mixture was stirred at 90°C for 3h, and then a modified silica solution, a fluorine-containing solution and / or a silylated epoxy resin were added, and the mixture was fully stirred at 90°C for 3h. After the reaction was completed, the mixture was dried at 30°C for 30h to obtain an organosilicon-modified polyurethane; an organosilicon-modified polyurethane A was prepared by adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution; an organosilicon-modified polyurethane B was prepared by adding a modified silica solution and a fluorine-containing solution; Step 3: In terms of mass fraction, 75% of silicone modified polyurethane A, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating A; 75% of silicone modified polyurethane B, 1% of dispersing agent, 0.5% of rheological agent, 7% of barium sulfate precipitate, 7% of talcum powder and 9.5% of anti-corrosion pigment are mixed and ground to obtain coating B; coating A is applied to the surface of the pretreated silicon steel sheet and cured at 200°C for 2h to obtain an adhesion layer with a thickness of 60μm; then coating B is applied and cured at 200°C for 2h to obtain a corrosion-resistant layer with a thickness of 100μm.
[0029] Comparative Example 4: The preparation step of the adhesion layer is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The silicon steel raw material is sequentially subjected to vacuum smelting at 1600°C for 40 minutes, hot rolling at 1100°C, normalizing heat treatment at 1000°C for 20 minutes, high-temperature heat treatment at 1000°C for 2 hours, cooling to 650°C and then cooling to 30°C by water quenching, tempering heat treatment at 300°C for 1 hour, and pickling treatment to obtain a pretreated silicon steel sheet; the silicon steel raw material includes 10wt% Si, 1wt% Cu, 0.6wt% rare earth element Ce, and 88.4wt% Fe; Step 2: Mix 2g of nano-silica filler and toluene, stir evenly to obtain a nano-silica solution; mix 5.5g of 3-mercaptopropyltrimethoxysilane and toluene, stir evenly to obtain a 3-mercaptopropyltrimethoxysilane solution; heat the nano-silica solution to 110°C, add the 3-mercaptopropyltrimethoxysilane solution, continue the reaction for 14h, and after the reaction is completed, centrifuge, purify, and dry to obtain modified nano-silica; 4 g of modified nano-silica was dissolved in 8 g of tetrahydrofuran to obtain a modified silica solution; 4.8 g of 2,3,5,6-tetrafluorophenylenedimethanol was dissolved in 10 g of tetrahydrofuran to obtain a fluorine-containing solution; 13g of polytetrahydrofuran and 25g of hydroxypropyl-terminated silicone oil were dried at 130°C, and then 0.005g of diisobutyltin dioctanoate, 25g of hexamethylene diisocyanate and 115g of tetrahydrofuran were added, and stirred for reaction at 90°C for 3h, and then modified silica solution and fluorine-containing solution were added, and stirred for 3h at 90°C. After the reaction was completed, the mixture was dried at 30°C for 30h to obtain silicone-modified polyurethane; Step 3: Mix and grind 75% silicone-modified polyurethane, 1% dispersing agent, 0.5% rheological agent, 7% barium sulfate precipitate, 7% talcum powder and 9.5% anti-corrosion pigment by mass fraction to obtain a coating; apply the coating to the surface of the pretreated silicon steel sheet, and cure it at 200°C for 2h to obtain a corrosion-resistant layer with a thickness of 100μm.
[0030] Adhesion performance test: The coating (coating A and / or coating B) prepared by the present invention is coated on one end of the substrate tinplate, and then epoxy glue is coated on the coating surface, and one end of another tinplate is bonded to one end of the above tinplate using epoxy glue. After being placed at 30°C for 2 days, the tinplate is fixed using a Zwick / RoellZ020 universal material testing machine, and the constant rate is set to 50 mm / min. The adhesion performance is evaluated by testing the shear tensile force.
[0031] Corrosion resistance test: The coating (coating A and / or coating B) prepared by the present invention was applied to the surface of a glass sheet, and after standing for 1 day, it was placed in an acid solution with pH=3 and an alkaline solution with pH=11 respectively. After immersion for 1 day, the water contact angle of the coating surface was measured, and the corrosion resistance was evaluated by testing the water contact angle. The results are shown in the following table:
[0032] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.
[0033] Comparative Example 1: The reaction mass ratio of modified silica and 2,3,5,6-tetrafluorophenylenedimethanol in the corrosion-resistant layer and the adhesion layer is adjusted to 1:0.7, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the water contact angle after acid corrosion is reduced to 119°, and the water contact angle after alkali corrosion is reduced to 109°. The reason is analyzed as follows: when the amount of 2,3,5,6-tetrafluorophenylenedimethanol in the corrosion-resistant layer and the adhesion layer is reduced, the surface energy of the prepared coating is increased, and it is more easily corroded by corrosive acids and alkalis, so the water contact angle is reduced and the corrosion resistance is reduced.
[0034] Comparative Example 2: The preparation step of the corrosion-resistant layer is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the water contact angle after acid corrosion is reduced to 110°, and the water contact angle after alkali corrosion is reduced to 102°. The reason is analyzed as follows: after removing the corrosion-resistant layer on the surface of the pretreated silicon steel sheet, the surface corrosion resistance of the pretreated silicon steel sheet is significantly reduced, so the water contact angle is reduced and the corrosion resistance is reduced.
[0035] Comparative Example 3: The reaction mass ratio of modified silica, 2,3,5,6-tetrafluorophenylenedimethanol and silylated epoxy resin in the adhesion layer is adjusted to 1:1.2:0.5, and the rest is the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the shear tensile force is reduced to 0.539 MPa. The reason is analyzed as follows: after reducing the amount of silylated epoxy resin in the adhesion layer, the adhesion of the adhesion layer is reduced, so the shear tensile force is reduced, and the coating is more likely to fall off.
[0036] Comparative Example 4: The preparation step of the adhesion layer is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the shear tensile force is reduced to 0.453 MPa. The reason is analyzed as follows: after removing the adhesion layer, the adhesion performance of the pretreated silicon steel sheet is significantly reduced, and the shear tensile force is significantly reduced.
[0037] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0038] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a rare earth metal element doped silicon steel sheet, characterized in that: The following steps are involved: Step 1: subjecting the silicon steel raw material to vacuum smelting, hot rolling, normalizing heat treatment, high temperature heat treatment, cooling water quenching, tempering heat treatment, and pickling treatment in sequence to obtain a pretreated silicon steel sheet; Step 2: Dry the polytetrahydrofuran and hydroxypropyl terminated silicone oil at 120-130° C., then add diisobutyltin dioctanoate, hexamethylene diisocyanate and tetrahydrofuran, stir and react at 80-90° C. for 2-3 hours, then add modified silica solution, fluorine-containing solution and / or silylated epoxy resin, stir well at 80-90° C. for 2-3 hours, and after the reaction is completed, dry at 25-30° C. for 25-30 hours to obtain silicone-modified polyurethane; By adding a modified silica solution, a fluorine-containing solution and a silylated epoxy resin solution, an organosilicon-modified polyurethane A is prepared; by adding a modified silica solution and a fluorine-containing solution, an organosilicon-modified polyurethane B is prepared; Step 3: mixing and grinding the organosilicon-modified polyurethane A, a dispersing agent, a rheological agent, a barium sulfate precipitate, talcum powder and an anticorrosive pigment to obtain a coating A; Mix and grind organosilicon-modified polyurethane B, a dispersing agent, a rheological agent, barium sulfate precipitation, talcum powder and an anticorrosive pigment to obtain coating B; Coating A is applied to the surface of the pretreated silicon steel sheet and cured at 180-200°C for 1-2h to obtain an adhesive layer; Then apply coating B and cure it at 180-200°C for 1-2h to obtain a corrosion-resistant layer.
2. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 1, characterized in that: In step 1, the silicon steel raw material includes 7-10wt% Si, 0.7-1.0wt% Cu, 0.3-0.6wt% rare earth elements, and the balance is Fe.
3. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 1, characterized in that: In step 1, the rare earth element is specifically any one of Ce, La, Y, Dy, and Nd; vacuum smelting: temperature is 1400-1600°C, time is 30-40min; hot rolling processing temperature is 900-1100°C; normalizing heat treatment: temperature is 900-1000°C, time is 10-20min; high temperature heat treatment: 900-1000°C, time is 1-2h; cooling water quenching treatment: cooling to 600-650°C and then cooling to 25-30°C by water quenching; tempering heat treatment: temperature is 200-300°C, time is 0.5-1h.
4. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 1, characterized in that: In step 2, the contents of the components of the organosilicon-modified polyurethane are as follows: by mass: 13-15 parts of polytetrahydrofuran, 25-30 parts of hydroxypropyl-terminated silicone oil, 0.005-0.007 parts of diisobutyltin dioctanoate, 18-25 parts of hexamethylene diisocyanate, 105-115 parts of tetrahydrofuran, 12-16 parts of modified silica solution, 14-19 parts of fluorine-containing solution and / or 18-28 parts of silanized epoxy resin solution.
5. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 4, characterized in that: When preparing organosilicon-modified polyurethane A, the reaction mass ratio of modified silica, 2,3,5,6-tetrafluorophenylenedimethanol and silylated epoxy resin is 1:1.2:(1.5-1.7); when preparing organosilicon-modified polyurethane B, the reaction mass ratio of modified silica and 2,3,5,6-tetrafluorophenylenedimethanol is 1:(1.2-1.4).
6. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 5, characterized in that: The modified nano-silicon dioxide is dissolved in tetrahydrofuran to obtain a modified silicon dioxide solution; 2,3,5,6-tetrafluorophenylenedimethanol is dissolved in tetrahydrofuran to obtain a fluorine-containing solution; and silylated epoxy resin is dissolved in acetone to obtain a silylated epoxy resin solution.
7. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 6, characterized in that: The preparation process of the silylated epoxy resin is as follows: in a nitrogen environment, epoxy resin and butyl acetate are mixed, heated to a liquid state at 40-50° C., 3-aminopropyltriethoxysilane is added, and the reaction is continued with stirring for 3-4 hours to obtain the silylated epoxy resin; wherein the reaction mass ratio of the epoxy resin, butyl acetate and 3-aminopropyltriethoxysilane is 10:1:(1.0-1.5).
8. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 6, characterized in that: The preparation process of the modified nano-silica is as follows: nano-silica filler and toluene are mixed, and the mixture is stirred evenly to obtain a nano-silica solution; 3-mercaptopropyltrimethoxysilane and toluene are mixed, and the mixture is stirred evenly to obtain a 3-mercaptopropyltrimethoxysilane solution; the nano-silica solution is heated to 100-110° C., the 3-mercaptopropyltrimethoxysilane solution is added, and the reaction is continued for 10-14 hours. After the reaction is completed, the modified nano-silica is obtained by centrifugation, purification, and drying. The reaction mass ratio of the nano-silica filler to the 3-mercaptopropyltrimethoxysilane is 2:(5-6).
9. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 1, characterized in that: In step three, the content of each component of coating A is: by mass fraction, 65-75% silicone modified polyurethane A, 0.7-1.0% dispersing aid, 0.3-0.5% rheological additive, 5-7% barium sulfate precipitate, 5-7% talcum powder, and the balance is anti-corrosion pigment; the content of each component of coating B is: by mass fraction, 65-75% silicone modified polyurethane B, 0.7-1.0% dispersing aid, 0.3-0.5% rheological additive, 5-7% barium sulfate precipitate, 5-7% talcum powder, and the balance is anti-corrosion pigment.
10. The method for preparing a rare earth metal element doped silicon steel sheet according to claim 1, characterized in that: In step three, the thickness of the adhesion layer is 40-60 μm, and the thickness of the corrosion-resistant layer is 90-100 μm.
Citation Information
Patent Citations
Preparation method of water-resisting durable silk fibroin modified silica coating
CN107936721A
Preparation method for high-tenacity, high-strength and non-oriented high-silicon steel
CN111155023A
Corrosion-resistant epoxy resin powder coating and preparation method thereof
CN118165622A
Rubber-coated steel wire for underwear and preparation method of rubber-coated steel wire
CN118727451A
An Improved Urethane Alkyd Resin
US20190330418A1